Factors influencing youth unemployment in Malaysia - Wong, Ning Qi (2024)
This research's objective is to examine the factors influencing youth unemployment in Malaysia from year 1991 to year 2022.This project studies the relationship between the gross domestic product, inflation rate, foreign direct investment and urbanization to the youth unemployment. The Vector Autoregression test has been chosen in this research.